Optimising the treatment of chronic ischemic heart disease by training general practitioners to deliver very brief advice on physical activity (OptiCor): protocol of the systematic development and evaluation of a complex intervention - Sabrina Hoppe; Alicia Prinz; Rik Crutzen; Norbert Donner-Banzhoff; Andrea Icks; Daniel Kotz; Oliver Kuß; Ute Mons; Markus Vomhof; Stefan Wilm; Sabrina Kastaun (BMC Primary Care)
Abstract Background Chronic ischemic heart disease (IHD) is one of the leading causes of morbidity and mortality. Physical activity (PA) is an effective secondary preventive strategy in IHD management. The German treatment guideline recommends that general practitioners (GPs) deliver PA advice to patients. This recommendation seems inadequately implemented, often due to GP’s insufficient specific training. International guidelines recommend training GPs in how to deliver such advice effectively and efficiently. Evidence is lacking on whether such training can enhance the frequency and quality of PA advice in routine care. The OptiCor project aims to develop and evaluate a GP training in the delivery of very brief PA advice to optimise the treatment of patients with IHD in general practice. Methods OptiCor comprises three study phases according to the Medical Research Council recommendations for developing and evaluating complex interventions. Phase 1 (needs analysis): A nationwide representative household survey will be conducted to collect data on the receipt of GP-delivered PA advice in people with IHD. Qualitative interviews and group discussions with GPs and people with IHD will help to explore, e.g., attitudes, experiences with, and barriers and facilitators of PA advice implementation or reception, respectively. Findings will inform the training development. Phase 2 (pilot): A pragmatic cluster randomised controlled trial (cRCT) on the effectiveness of the developed training on proportions of GP-delivered PA advice during routine care of IHD patients will be piloted. Phase 3 (evaluation): A full pragmatic cRCT will be conducted with patient-reported proportions of GP-delivered PA advice as primary endpoint. Collection of health economic and process-related data will facilitate a potential future broad implementation and health economic evaluation of the training. Discussion If the developed training successfully improves proportions and quality of GP delivered PA advice to patients with IHD, it could serve as a low-threshold and sustainable strategy for implementing PA recommendations in the secondary prevention of IHD in routine GP practice. Trial registration Work package (WP) 1, WP5, and WP6 have been prospectively registered at German Clinical Trials Register (WP1: DRKS00031304, 19/06/2023; WP5: DRKS00034641, 10/07/2024; WP6: DRKS00034642; 10/07/2024).